Origin and Emplacement of the Cambrian Yanglong Ophiolite in the North Qilian Suture - FU, Changlei; XUE, Wanwen; PAN, Tong; YAN, Zhen; GUO, Xianqing; AITCHISON, Jonathan C.; XIAO, Wenjiao; WANG, Bingzhang; LI, Wufu (Acta geologica Sinica (Beijing), 2025)
Fragments of Proto‐Tethyan oceanic lithosphere are well‐preserved along the southern belt of the North Qilian suture, and the origin and emplacement of these ophiolites have become subjects of intense debate. In this study, we integrate field observations, mineralogical and geochemical analyses, zircon U‐Pb dating, and isotopic data to investigate the Yanglong ophiolite. The Yanglong ophiolitic rocks are found as tectonic slices resting on the Neoproterozoic sedimentary and volcanic rocks. These rocks are composed of Cambrian serpentinized peridotite, gabbro, dolerite, and rodingite. The spinels in the serpentinized peridotites have variable Cr# values (21, 38–46, and 59–61) and display affinity to those in abyssal and forearc peridotites. The dolerites show slight enrichment in Th and have elevated (La/Sm)N ratios (1.19–2.01), indicating a subduction‐related geochemical affinity. The Yanglong ophiolitic rocks have positive zircon εHf(t) values (+10.3 to +18.4) and whole‐rock εNd(t) values (+5.3 to +6.7) indicating derivation from partial melting of a depleted mantle source. These results, together with the regional geology, collectively suggest that the Yanglong ophiolite was generated in a forearc setting during the Early Cambrian northward intra‐oceanic subduction. It was emplaced onto the Central Qilian Block during the subsequent arc–continent collision, no later than the Early Ordovician.